ANALISIS STRATEGI PEMASARAN USAHA KECIL MENENGAH PADA MASA PANDEMI CORONA VIRUS (COVID-19) (STUDI KASUS UKM “TAHU BAKSO BERKAH SENTOSA SIDOARJO) - Santoso (STAI AN-NAJAH INDONESIA MANDIRI, 2021)
According to the minister of PPN/Bappenas, Indonesia experienced an economic growth of 0.05% due to the existence of UKM. People who have independent businesses are one of the strategies to move the wheels of the nation's economy. The Covid-19 pandemic situation provides challenges and opportunities for the Indonesian government to maintain the existence of UKM.Therefore, a short-term solution is needed for UKM and the workers who are members of them. This study aims to describe: 1. The marketing strategy applied by UKM